2020
DOI: 10.3389/fnins.2020.00884
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT6 Receptors in the Ventrolateral Orbital Cortex Attenuate Allodynia in a Rodent Model of Neuropathic Pain

Abstract: Mechanical allodynia, characterized by a painful sensation induced by innocuous stimuli, is thought to be caused by disruption in pain-related regions. Identification and reversal of this pathologic neuroadaptation are therefore beneficial for clinical treatment. Previous evidence suggests that 5-HT 6 receptors in the ventrolateral orbital cortex (VLO) are involved in neuropathic pain, but their function is poorly understood. The aim of the present study is to unveil the role of 5-HT 6 receptors in the VLO and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The injection times, i.e., single injection of TSA versus repeated TSA injection throughout the development phase, might partially explain the discrepancy. Moreover, this result is reminiscent of other VLO studies, in which the microinjection of the 5-HT6 receptor agonist into the VLO aggregated acute inflammatory pain and attenuated chronic neuropathic pain [33,34]. Different cell types, such as glutamatergic versus GABAergic neurons, and dopamine D1 receptor-expressing (D1R) neurons versus D2R neurons, exhibited different, and even opposing effects on drug-related behaviors.…”
Section: The Tsa Has Opposing Effects On Acute Versus Chronic Morphin...mentioning
confidence: 52%
“…The injection times, i.e., single injection of TSA versus repeated TSA injection throughout the development phase, might partially explain the discrepancy. Moreover, this result is reminiscent of other VLO studies, in which the microinjection of the 5-HT6 receptor agonist into the VLO aggregated acute inflammatory pain and attenuated chronic neuropathic pain [33,34]. Different cell types, such as glutamatergic versus GABAergic neurons, and dopamine D1 receptor-expressing (D1R) neurons versus D2R neurons, exhibited different, and even opposing effects on drug-related behaviors.…”
Section: The Tsa Has Opposing Effects On Acute Versus Chronic Morphin...mentioning
confidence: 52%
“…Moreover, intrathecal injection of PKA inhibitor H89 30 min before EA reversed the EA effect on the tactile withdrawal thresholds. Our previous and preliminary studies found that AC inhibitor SQ22536 or PKA inhibitor H89 alone has any effect on the pain threshold in the central (Zhang et al, 2020) and spinal cord, which suggested that the AC-cAMP-PKA pathway may lack tonic activity, and the blocking effects of AC and PKA inhibitor on the EA-evoked inhibition were not a result of either compound facilitating nociceptive responses. These data further support that EA activates the spinal 5-HT 7 receptor through the Gs-AC-cAMP-PKA pathway to inhibit chronic pain in a mouse model of KOA.…”
Section: Figure 6 |mentioning
confidence: 91%